Possible heating effect in the mesospheric 51 to 70 km altitude region over Thumba (8° N, 77° E) following geomagnetic activity - SESHAMANI, R. (MAUSAM, 1980)
The variation in equatorial mesospheric temperatures at altitudes of 51 to 70 km during geomagnetically-active periods has been studied. A correlation analysis of rocketsonde temperature data obtained from the M-100 sounding rocket launchings at Thumba (8 deg. N, 77 deg. E) and the daily planetary geomagnetic index Ap has been carried out for a one-year period (December 1970 to December 1971). The results of the analysis reveal a highly significant in-phase relationship between the temperatures and Ap . The 51 to 70 km layer average temperature changes in-phase, around 3 to 4 days after the Ap increase. The temperature change has been quantified by (DELTA)T/(DELTA)Ap = 0.36° K (approx.) for a four-day lag between the time of Ap increase and the subsequent temperature increase. This heating effect in the 51 to 70 km altitude region around 3 to 4 days after variations in geo-magnetic activity, appears to be a part of the phenomenon of solar/geomagnetic activity induced perturbations in the equatorial neutral atmosphere over Thumba, observed by Raja Rao et al. (1978). Such results would form useful inputs for modelling the neutral atmosphere over India.